Nanosized Co3O4/SiO2 for heterogeneous oxidation of phenolic contaminants in waste water - Shukla, Pradeep; Sun, Hongqi; Wang, Shaobin; Ang, Ha Ming; Tade, Moses (Pergamon, 2011)
Nanosized silica supported Co catalysts were prepared using three different Co(II) precursor salts, nitrate (N), chloride (Cl) and acetate (Ac). The physicochemical properties of the three Co/SiO2 catalysts were characterized by several techniques, such as XRD, SEM, TEM, FT-IR, FT-Raman and UV–vis diffuse reflectance spectroscopy, and the catalytic activity in heterogeneous activation of peroxymonosulphate to produce sulphate radicals for phenol degradation was investigated. It was found that anions of Co precursor affected the interaction between Co metal and support, influencing the properties of the catalysts and their catalytic activity. All three Co/SiO2 catalysts exhibited high activity in sulphate radical generation and phenol degradation. The Co/SiO2 prepared using Co nitrate showed a strong Co and support interaction by forming Co3O4 and Co2SiO4 species and exhibited less leaching of Co. The rate of phenol oxidation on Co/SiO2 followed an order of Co/SiO2–Cl > Co/SiO2–Ac > Co/SiO2–N while the stability of the three catalysts presented an opposite trend. Co/SiO2–N still exhibited higher activity after three-run tests while the other two catalysts showed significant deactivation. Phenol degradation on Co/SiO2 followed zero order kinetics and activation energies of Co/SiO2–N, Co/SiO2–Cl, Co/SiO2–AC were obtained as 67.5, 75.1 and 61.7 kJ/mol, respectively.